Breastfeeding practice among women with an infant of 1 year old and below in the District of Hilir Perak, 1994 - Rosli Ismail; Hashami Bohari; Khalib Latip (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
The trend of breastfeeding is said to be on the decline in most developing countries. It has been associated with the rapid developments and the changes in the socio-economic status of a country. The objective of this study is to determine the present practice of breast feeding in a rural community and identify associated socio-demographics factors. This is a cross-sectional study whereby 185 mothers attending the various child health clinics in the district, were selected and interviewed using a pretested questionnaires. It was found that 51% of respondents practised breast feeding at the birth of their child, whereas only 30% were currently breastfeeding. Majority of respondents (60%) have a family income of RM500 and below per month and 63% have a higher educational status. About 75% of mothers were unemployed and breastfeeding practised among them were only 38%. There were significant relationship between variables such as educational status, family income, mother's parity and ethnicity with breast feeding practices. Majority of respondents obtained a high score on knowledge and positive attitudes toward breastfeeding practices. Among 51 respondents with one child, breastfeeding practised was only 20%. The main reason given for practising mixed feeding is insufficient breast milk; and among those who practised bottle feeding, majority chose absence of breast milk as their main reason. In most studies it was found that factors which may increase the breastfeeding pattern of a community, may decrease it in another community. In this study, we will identify the "risk groups" (those mothers not practicing breastfeeding) , so that a more comprehensive health education programmes could be planned to increase and promote breast feeding effectively. In general, breastfeeding practice is on the decline in both the urban and rural communities.